Early Noise-Induced Hearing Loss Accelerates Presbycusis Altering Aging Processes in the Cochlea - Fetoni, Anna Rita; Pisani, Anna; Rolesi, Rolando; Paciello, Fabiola; Viziano, Andrea; Moleti, Arturo; Sisto, Renata; Troiani, Diana; Paludetti, Gaetano; Grassi, Claudio (Frontiers in Aging Neuroscience, 2022)
Several studies identified hearing loss as a risk factor for aging-related processes, including neurodegenerative diseases, as dementia and age-related hearing loss (ARHL). Although the association between hearing impairment in midlife and ARHL has been widely documented by epidemiological and experimental studies, the molecular mechanisms underlying this association are not fully understood. In this study, we used an established animal model of ARHL (C57BL/6 mice) to evaluate if early noise-induced hearing loss (NIHL) could affect the onset or progression of age-related cochlear dysfunction. We found that hearing loss can exacerbate ARHL, damaging sensory-neural cochlear epithelium and causing synaptopathy. Moreover, we studied common pathological markers shared between hearing loss and ARHL, demonstrating that noise exposure can worsen/accelerate redox status imbalance (increase of ROS production, lipid peroxidation and dysregulation of endogenous antioxidant response) and vascular dysfunction (increased expression of HIF-1α and VEGFC) in the cochlea. Unveiling molecular mechanisms underlying the link between hearing loss and aging processes could be valuable to identify effective therapeutic strategies to limit the effect of environmental risk factors on age-related diseases.